Pendampingan UMKM Tusuk Gigi Dusun Tegal Jaya Desa Batumarta I Melalui Pemanfaatan Media Sosial dan Pencatatan Keuangan Sederhana (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2026)
Toothpick MSMEs in Tegal Jaya Hamlet, Batumarta I Village, still face challenges in product marketing and business financial management. Product marketing has not utilized social media due to limited knowledge and skills of MSME owners, while business financial records have not been systematically recorded despite the separation of personal and business finances. This mentoring activity aims to increase the capacity of MSME owners to utilize social media as a promotional tool and implement simple financial records. The implementation method includes socialization, interviews, training, and direct mentoring focused on creating social media promotional content and recording business income and expenses. The results of the activity indicate an increase in understanding and skills of MSME owners in using social media for product promotion and compiling financial records in a more orderly and systematic manner. This mentoring is expected to increase marketing effectiveness, support more planned business management, and encourage the sustainability of toothpick MSMEs in Tegal Jaya Hamlet.